Analysis of Judges' Decision on Witness Divorce Evidence in Donggala Religious Court - Usman Usman; Abidin Abidin; Lukman S. Thahir (State Institute for Islamic Studies Palu, 2022)
A judge's decision or commonly called court decision, is a written statement made by a judge as a government official who has been authorized to do so. The statement is made in a court case and it is open to the public after going through procedural law processes, to resolve or end a case to create legal certainty and justice for the disputing parties. This study used a qualitative case study approach. Data was collected through direct observation, in-depth interviews, and written material analysis. The results of this study show that the judges examining, deciding, and resolving divorce cases based on Indonesia marraige laws and regulations. Witness evidence considered by the Panel of Judges is a witness that meets the formal and material requirements. One of the material requirements is that the witness testifies to what he has seen, heard, and experienced, not to hear other people's stories. Civil procedural law witnesses who do not personally witness an event which is the reason for the parties to a lawsuit in court, is called de auditu testimony.